Updated pelagic nitrogen budget of the Amazon and Pará estuaries of METEOR cruise M174 - Noémie Choisnard; Jacqueline Umbricht; Maren Voss (PANGAEA, 2024)
The Amazon River is known as a region of intense biochemical reactivity. As a result of increased anthropogenic impacts in its catchment (e.g. population growth, agriculture, and deforestation), The Amazon River is undergoing fundamental changes. The RV METEOR cruise M174 (doi:10.1594/PANGAEA.935041) aimed to provide an integrated overview of nitrogen cycling processes in areas influenced by the Amazon River, which is crucial to estimate the ecosystem extquotesingles health and productivity. During this cruise, six stations were visited to create an updated nitrogen budget of the Amazon and Pará estuaries. This dataset presents the results of the budget calculated for 6 stations of varying turbidity. Nitrification, nitrate, ammonium and amino acid uptake rates (in mol/day) are taken into account in this budget, and compared to riverine dissolved inorganic nitrogen inputs. Dissolved inorganic carbon uptake rates are also presented.